Pandemic designs for the future: perspectives of technology education teachers during COVID-19. Issue 5 (8th July 2020) - Code, Jillianne; Ralph, Rachel; Forde, Kieran
Abstract : Purpose: The disruption caused by the pandemic declaration and subsequent public health measures put in place have had a substantial effect on teachers' abilities to support student engagement in technology education (TE). The purpose of this paper is to explore the following research question: How do TE teachers see emergency remote teaching (ERT) transitions to blended learning into the next academic year affecting their profession? Design/methodology/approach: A snowball and convenience sampling design was used to recruit specialist teachers in TE through their professional organization and were asked to respond to the question: What are your concerns about the future of teaching TE remotely? The qualitative data collected from the participants (N = 42) was analyzed thematically (Braun and Clarke, 2006). Findings: The analysis revealed that the switch to ERT impacted the teachers' ability to support hands-on competency development owing to inequitable student access to tools, materials and resources, all of which affected student motivation and engagement. As a result, teachers raised questions about the overall effectiveness of online learning approaches and TE's future and sustainability if offered completely online. Originality/value: This research is the first of its kind exploring the experiences of TE teachers during the COVID-19 pandemic. In answer to the challenges identified by teachers, the authors offer a blended learning design framework informed by pandemic transformed pedagogy that can serve as a model for educators to use when designing blended instruction.